A localized tracing technique to explore intra-amygdala functional and structural correlates of individual variability in behavioral response - Lipshutz, Allie; Saltz, Victoria; Anderson, Kristin R.; Manganaro, Alessia; Dumitriu, Dani (Frontiers in Molecular Neuroscience, 2025)
IntroductionThe neurobiological basis for individual variability in behavioral responses to stimuli remains poorly understood. Probing the neural substrates that underlie individual variability in stress responses may open the door for preventive approaches that use biological markers to identify at-risk populations. New developments of viral neuronal tracing tools have led to a recent increase in studies on long range circuits and their functional role in stress responses and social behavior. While these studies are necessary to untangle largescale connectivity, most social behaviors are mediated and fine-tuned by local subregional circuitry.MethodsIn order to probe this local, interregional connectivity, we present a new combination of a neuronal tracing system with immediate early gene immunohistochemistry for examining structural and functional connectivity within the same animal. Specifically, we combine a retrograde transsynaptic rabies tracing system with cFos colocalization immediately after an acute stressor to elucidate local structural and stress-activated connectivity within the amygdala complex in female and male mice.Results and discussionWe show how specific structural and functional connections can predict individual variability along a spectrum of social approach/avoidance following acute social defeat stress. We demonstrate how our robust method can be used to elucidate structural and functional differences in local connectivity that mediate individual variability in behavioral response.